Book review: Bilingualism (GIST – Education and Learning Research Journal, 2024)
This review delves into Mahootian’s (2020) comprehensive textbook on bilingualism. The text is praised for its systematic exploration of the topic, addressing various facets of bilingualism across five distinct chapters, culminating in a final chapter that ties together and reiterates the main points from each prior section. Particularly lauded is the author’s emphasis on the future of research in the fields of psycholinguistics and neurolinguistics. Mahootian’s exceptional integration of complex theories, paired with her accessible writing style, marks the textbook as a valuable resource for the academic community.